A porous GaN/MoO3 heterojunction for filter-free, ultra-narrowband ultraviolet photodetection. Issue 13 (3rd March 2022) - Guo, Yue; Song, Weidong; Liu, Qing; Sun, Yiming; Chen, Zhao; He, Xin; Zeng, Qingguang; Luo, Xingjun; Zhang, Ruiqing; Li, Shuti
Abstract : A porous GaN/MoO3 heterojunction ultraviolet photodetector with visible-blind, filter-free and ultra-narrowband (FWHM <10 nm) response is presented. This narrowband ultraviolet photodetector is promising for secure communication applications. Abstract : Commonly, a narrowband photodetector that can detect specific wavelengths is obtained by integrating a broadband photodetector with an external optical filter. However, this integration significantly increases the structural complexity and cost, and reduces the sensitivity. Herein, we demonstrate a filter-free, ultra-narrowband, ultraviolet photodetector based on a porous GaN/MoO3 heterojunction. Porous GaN with reduced defects and enhanced light trapping was fabricated by a facile photoelectrochemical etching method. The optimized porous GaN/MoO3 photodetector shows visible-blind (peaked at 370 nm) and ultra-narrowband (FWHM <10 nm) ultraviolet photoresponse. Moreover, the photodetector exhibits a large light-to-dark current ratio (nearly 10 5 at −3 V), along with a remarkable responsivity, external quantum efficiency, and detectivity of 187.5 mA W −1, 62.8%, and 4.34 × 10 12 Jones, respectively. The highly-performing and narrowband response makes the porous GaN/MoO3 ultraviolet photodetector promising for secure optical communication systems.